Bioeconomy study of mackerel (rastrelliger spp) in belawan Gabion ocean fishing port Medan city north sumatera province - Isrofiah, Nur; Bathara, Lamun; ', Hendrik (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research on bioeconomy mackerel was held on March 23, 2014 untilApril 4, 2014 at Belawan Ocean Fishing Port. Aimed of this research was todetermine the potential magnitude of mackerel fisheries resources throughbioeconomy analysis that includes biological aspects (MSY) and economicaspects (MEY) and utilization level of mackerel.This study used surveymetodhology by purposive sampling to 5 people that use purse seine.Results of the research showed that the arrestable of the biological aspectsof mackerel that able to catch was 202.44 tonnes with 2098 trips in effort, whilethe economic aspect, mackerel which must be captured in order to earn a profit of199.98 tonnes by 2091 trip in effort at the same time. Based on bioeconomyanalysis, the next effort was reducted the effort level 6459 trips and number ofthe catch 4759 tonnes in order to suistainable return waters resources. It is alsodiscovered the mackerel utilization rate in Belawan Ocean Fishing Port was96.00% which was overfishing.The Keyword: Bioeconomy, mackerel, Belawan Ocean Fishing Port